Lewis Acid Catalysed Asymmetric One-Carbon Ring-Expansion of Prochiral Cyclobutanones - Tenberge, Marius; Wahl, Johannes M. (Synthesis, 2022)
Enantioselective methylene insertion into prochiral cyclobutanones is described providing access to chiral β-substituted cyclopentanones as important structural motif in synthesis and natural products. Commercially available trimethylsilyl as well as other silyl diazomethanes act as one-carbon synthon and scandium triflate is found to be a potent Lewis acid catalyst. By using bis(oxazoline) ligands, enantioinduction is achieved for a number of β-substituted cyclopentanones including examples bearing all-carbon quaternary stereocentres.
Keywords: desymmetrisation; ring expansion; prochiral cyclobutanones; chiral cyclopentanones; bis(oxazoline) ligand; strain release